The non-death role of metacaspase proteases - Shrestha, Amit; Megeney, Lynn A. (Frontiers in Oncology, 2012)
The activation of caspase proteases and the targeting of protein substrates act as key steps in the engagement and conduct of apoptosis/programmed cell death. However, the discovery of caspase involvement in diverse non-apoptotic cellular functions strongly suggests that these proteins may have evolved from a core behavior unrelated to the induction of cell death. The presence of similar proteases, termed metacaspases, in single cell organisms supports the contention that such proteins may have co-evolved or derived from a critical non-death function. Indeed, the benefit(s) for single cell life forms to retain proteins solely dedicated to self destruction would be countered by a strong selection pressure to curb or eliminate such processes. Examination of metacaspase biology provides evidence that these ancient protease forerunners of the caspase family also retain versatility in function, i.e., death and non-death cell functions. Here, we provide a critical review that highlights the non-death roles of metacaspases that have been described thus far, and the impact that these observations have for our understanding of the evolution and cellular utility of this protease family.